Energy Efficiency Comparison of ECBC–2023 and IECC–2021 for Residential Buildings in Different Climate Zones of Pakistan - Muhammad Osama Aziz; Muhammad Abbas; Fakhre Alam Khan; Naveed Ahmad; Fazli Yazdan; Hamad Aftab; Mohammad Irshad Khan; Zahid Ullah (Engineering Reports)
ABSTRACT This study presents a comparative analysis of the energy‐saving potential of the newly developed Pakistani regulation, the Energy Conservation Building Code–2023, and the International Energy Conservation Code–2021 for residential buildings in Pakistan. Utilizing an EnergyPlus‐based simulation tool, the energy consumption of a typical house was modeled in three different climate zones of Pakistan: 0B (hot and dry), 3B (warm dry), and 7B (very cold). The analysis focused on evaluating how improvements in the building envelope, as mandated by each code, impacted the overall energy consumption of the building. Results revealed that the Energy Conservation Building Code–2023 performs better than the International Energy Conservation Code–2021 in hot climates such as Karachi. Specifically, the Energy Conservation Building Code–2023 achieved a 24% reduction in annual energy consumption, compared to the 21.8% reduction achieved by the International Energy Conservation Code–2021. However, the International Energy Conservation Code–2021 demonstrates higher energy savings in warm and cold climates (Quetta and Skardu). In these zones (warm 3B and very cold 7B), the International Energy Conservation Code–2021 led to reductions of 47.32% and 79.5%, respectively, compared to 45.3% and 33.86% achieved by the Energy Conservation Building Code–2023. This variation in energy‐saving potential is attributed to the stringent U‐value standards set by the International Energy Conservation Code–2021, particularly for colder climates. The study evaluates the strengths and limitations of both codes concerning Pakistan's diverse climatic conditions, underscoring the need for region‐specific energy conservation standards to optimize residential building efficiency. It highlights the necessity for ongoing Research and Development to enhance the effectiveness and nationwide applicability of the Energy Conservation Building Code–2023.